Bilateral Ear Canal Cholesteatoma with Underlying Type I First Branchial Cleft Anomalies. (April 2019) - Banakis Hartl, Renee M.; Said, Sherif; Mann, Scott E.
Objectives: To describe a case of bilateral ear canal cholesteatomas in the setting of underlying first branchial cleft cyst anomalies and to review the pathophysiology underlying the development of external auditory canal cholesteatomas from branchial cleft cyst abnormalities. Methods and Results: We present a case study of a 61-year-old man who presented with chronic right-sided hearing loss and left-sided postauricular drainage. Clinical evaluation, radiographic work-up, and pathologic analysis confirmed a diagnosis of bilateral ear canal cholesteatoma in the setting of underlying first branchial cleft cyst anomalies. The patient's clinical course, surgical treatment, and management considerations are discussed here. Conclusion: Ear canal cholesteatoma represents a rare clinical disease entity deserving a thorough initial assessment. Careful consideration of underlying diseases that result in chronic inflammation, such as branchial cleft lesions, should be included in the differential diagnosis of idiopathic canal cholesteatoma in the absence of prior otologic surgery or trauma.